PERMEABILITY OF INTERLANGUAGE SYSTEM: A CASE STUDY OF STUDENTS LEARNING ENGLISH AS A FOREIGN LANGUAGE AT SMP MUHAMMADIYAH 5 SURAKARTA - Lestari Kelik Maryana (Jurnal Penelitian Humaniora, 2016)
The research deals with permeability of students’ interlanguage system that reflects in students’ composition of SMP Muhammadiyah 5 Surakarta. The aims of the research are (1) to describe what the types of permeability, (2) to describe the sourceof the influence in students’ IL system, and (3) to describe the influence frequency of students’ IL system. The type of this research is qualitative research. The data of this research are erroneous sentences found in the students’ compositions. The method of collecting data is elicitation and document analysis. The writer uses descriptive analysis by Celce Marcia and a modified framework of Error Analysis by Shridar a technique for analyzing data. The results indicate that (1) the permeability is found atthe level of morphology and syntax, (2) the source of the influence is students’ mother tongue (Indonesian) and target language (English), (3) the influence frequency of the mother tongue to students’ interlanguage system is 48% and of the target languageto the students’ interlanguage system is 52%. The conclusion is that the learners’ interlanguage is open to to influence from the outside and influence from the inside language system. It progressively approaches the target language as a result oflearners’ attempt on constructing a new linguistic system.